2013
DOI: 10.1038/srep02723
|View full text |Cite
|
Sign up to set email alerts
|

The boundary of the meristematic and elongation zones in roots: endoreduplication precedes rapid cell expansion

Abstract: Plant roots consist of a meristematic zone of mitotic cells and an elongation zone of rapidly expanding cells, in which DNA replication often occurs without cell division, a process known as endoreduplication. The duration of the cell cycle and DNA replication, as measured by 5-ethynyl-2′-deoxy-uridine (EdU) incorporation, differed between the two regions (17 h in the meristematic zone, 30 h in the elongation zone). Two distinct subnuclear patterns of EdU signals, whole and speckled, marked nuclei undergoing D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 45 publications
2
122
0
Order By: Relevance
“…4H-J). Additionally, this discrepancy can be explained by the observation that in arabidopsis roots the endoreduplication cycle can also start in the EZ and that its duration is greater than that of the cell cycle in the RAM (Hayashi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4H-J). Additionally, this discrepancy can be explained by the observation that in arabidopsis roots the endoreduplication cycle can also start in the EZ and that its duration is greater than that of the cell cycle in the RAM (Hayashi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, before rapid elongation, the symplastic nature of plant tissues yields a domain at which cells start endoreduplication but do not start rapid elongation; this region then corresponds to the TD (Baluska et al, 1996;Ivanov and Dubrovsky, 2013). Indeed, experimental evidence has shown that in arabidopsis endoreduplication precedes rapid cell elongation (Hayashi et al, 2013). Thus, for a particular cell file within the arabidopsis root, the TD can also be defined as the region where cells endoreduplicate and continue elongating at the same rate as in the PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay was also used to differentiate cells in early and late Sphase in root tips of Arabidopsis seedlings (Hayashi et al, 2013). The assay was successfully applied in alfalfa suspension cultured cells and root tips (Bazin et al, 2013), tomato root tips (Ron et al, 2013;Kuznetsova & Sheval', 2013), field bean root tips (Schubert et al, 2011), asparagus cladodes (Nakayama et al, 2012), tobacco suspension cultured cells (Tresch et al, 2011), rice suspension cultured cells (Dudits et al, 2011) and maize root tips (Bass et al, 2014).…”
Section: Edu and Click Chemistrymentioning
confidence: 99%